Moderasi Beragama di Tengah Cyber-Religion dan COVID-19: (Studi terhadap Mahasiswa Fakultas Ushuluddin IAIN Kudus) - Mundakir, Akhmad (FIKRAH, 2021)
This article examines religious phenomena on social media. The rise of speakers on social media gives a new color to modern religious issues, as it relates to the issue of religious moderation. because the media is often used to invite and teach religious teachings in a right and rigid so that it becomes a cyber-religion that can not be accounted for its authority. This reality received many responses from the community, including students of the Faculty of Ushuluddin IAIN Kudus. This article is a qualitative study that reveals the perception of Students of Fakultas Ushuluddin on religious moderation in the midst of the media and pandemic. This article concludes that the religious cyber phenomenon is a consequence of the rise of religious preachers on social media. Amid covid-19, religious lectures also contain pandemic themes that are sometimes provocative and construction